2007
DOI: 10.1111/j.1540-8175.2007.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Left Ventricular Myocardial Involvement and Endothelial Dysfunction in Systemic Sclerosis: Noninvasive Assessment in Asymptomatic Patients

Abstract: Strain rate imaging, transthoracic CFR, and brachial artery flow-mediated dilatation are valuable noninvasive and easily repeatable tools for detecting LV myocardial and vascular involvement caused by SSc. Their combined use may be therefore useful for early identifying patients with more diffused and severe form of SSc, ideally in asymptomatic cases prior to the development of severe vasculopathy, when it may be most feasible to modify the disease process by new potential therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…[24] This is consistent with other studies where strain imaging has been shown to be useful in the early detection of myocardial involvement in asymptomatic patients with diabetes, systemic sclerosis, amyloidosis, and doxorubicin-induced cardiomyopathy. [25262728] CMR strain and strain rate imaging may be a more sensitive indicator of myocardial involvement also in Kawasaki disease patients, both in the acute and convalescent phases. To our knowledge, this is the first study to apply CMR-FT in Kawasaki disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…[24] This is consistent with other studies where strain imaging has been shown to be useful in the early detection of myocardial involvement in asymptomatic patients with diabetes, systemic sclerosis, amyloidosis, and doxorubicin-induced cardiomyopathy. [25262728] CMR strain and strain rate imaging may be a more sensitive indicator of myocardial involvement also in Kawasaki disease patients, both in the acute and convalescent phases. To our knowledge, this is the first study to apply CMR-FT in Kawasaki disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Along with multiple reports of RV abnormalities in SSc, usually secondary to vascular and interstitial lung disease resulting into pulmonary hypertension [19,20], a primary LV involvement related to organic and functional alterations of microvasculature, including reduced coronary flow reserve, has been observed [21-24]; in support of these data, studies performed using single photon emission computerized tomography (SPECT) have shown multiple ventricular perfusion defects in the absence of coronary artery disease documented by angiography, particularly in patients with pulmonary hypertension [25,26]. Owing to this vasculopathy, a “patchy” myocardial fibrosis develops, with a distribution unrelated to coronary vessels territories [27-30], leading, as consequences, to multiple LV diastolic and systolic abnormalities including lower TDI velocities and impaired myocardial deformation [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of myocardial strain and SR has been used to identify early systolic impairment in arterial hypertension [89], asymptomatic mitral regurgitation [90], pulmonary hypertension [91], rejection after HTX [92], congenital cardiac abnormalities [93], obesity [94], subclinical atherosclerosis [95], and in a number of systemic diseases [96,97]. Strain can discriminate between hypertensive cardiomyopathy and nonobstructive hypertrophic cardiomyopathy [98].…”
Section: Clinical Applicationsmentioning
confidence: 99%